Radiochemical and radiopharmacological characterization of a 64Cu‐labeled α‐MSH analog conjugated with different chelators. (17th June 2019) - Gao, Feng; Sihver, Wiebke; Bergmann, Ralf; Walther, Martin; Stephan, Holger; Belter, Birgit; Neuber, Christin; Haase‐Kohn, Cathleen; Bolzati, Cristina; Pietzsch, Jens; Pietzsch, Hans‐Jürgen
Abstract : Radiolabeled α‐melanocyte‐stimulating hormone (α‐MSH) derivatives have a high potential for diagnosis and treatment of melanoma, because of high specificity and binding affinity to the melanocortin‐1 receptor (MC1R). Hence, the α‐MSH‐derived peptide NAP‐NS1 with a β‐Ala linker (ε‐Ahx‐β‐Ala‐Nle‐Asp‐His‐D‐Phe‐Arg‐Trp‐Gly‐NH2 ) was conjugated to different chelators: either to NOTA ( p ‐SCN‐Bn‐1, 4, 7‐triazacyclononane‐1, 4, 7‐triacetic acid), to a hexadentate bispidine carbonate derivative (dimethyl‐9‐(((4‐nitrophenoxy)carbonyl)oxy)‐2, 4‐di(pyridin‐2‐yl)‐3, 7‐bis(pyridin‐2‐ylmethyl)‐3, 7‐diazabicyclo[3.3.1]nonane‐1, 5‐dicarboxylate), or to DMPTACN (p‐SCN‐Ph‐bis(2‐pyridyl‐methyl)‐1, 4, 7‐triaza‐cyclononane), labeled with 64 Cu, and investigated in terms of radiochemical and radiopharmacological properties. For the three 64 Cu‐labeled conjugates negligible transchelation, suitable buffer and serum stability, as well as appropriate water solubility, was determined. The three conjugates exhibited high binding affinity (low nanomolar range) in murine B16F10, human MeWo, and human TXM13 cells. The B max values of [ 64 Cu]Cu‐bispidine‐NAP‐NS1 ([ 64 Cu]Cu‐2 ) and [ 64 Cu]Cu‐DMPTACN‐NAP‐NS1 ([ 64 Cu]Cu‐3 ) were higher than those of [ 64 Cu]Cu‐NOTA‐NAP‐NS1 ([ 64 Cu]Cu‐1 ), implying that different charged chelate units might have an impact on binding capacity. Preliminary in vivo biodistribution studies suggested the main excretion pathway of [ 64 Cu]Cu‐1 and [ 64 Cu]Cu‐3 to be renal, while that of [ 64 Cu]Cu‐2 seemed to be both renal and hepatobiliary. An initial moderate uptake in the kidney decreased clearly after 60 minutes. All three 64 Cu‐labeled conjugates should be considered for further in vivo investigations using a suitable xenograft mouse model. Abstract : 64 Cu‐ labeled NAPamide conjugates with three different chelators showed good stability, low trans chelation, and high affinity to MC1 receptors in murine and human melanoma cells. Preliminary in vivo studies support the application of the three radioconjugates in a melanoma‐bearing mouse model.